"And yet your duty is to hope": The positive psychology of Jean-Paul Sartre. (June 2016) - Quackenbush, Steven W.; Lockwood, Alanah K.; Cyr, Travis G.
In this article, we consider the potential relevance of the philosophy of Jean-Paul Sartre to the positive psychology movement. Specifically, we argue that Sartre's consideration of freedom as the "foundation of all values" can be read as a defense of generosity as the cardinal psychosocial virtue. For Sartre, authentic existence is not simply a quest to realize subjective well-being or to acquire a collection of conventional virtues and character strengths. Rather, authenticity is most appropriately understood as a life (holistically conceived) offering itself as a gift to the Other—a freedom realizing its humanity by nurturing other freedoms . Practical implications of Sartrean thought are considered, with special attention given to "gratitude" as an erstwhile character strength that potentially undermines the quest for freedom.